Analysis of the Effectiveness of the Assessment and Evaluation System in Higher Education within the Environment of Okmin University - Kulka, Serius; Nabyal, Mayxsie T. (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to conduct an in-depth analysis of the effectiveness of the assessment and evaluation system in higher education within the environment of Okmin University. With the dynamic growth in the field of higher education, it becomes crucial to evaluate the extent to which the current assessment system achieves its evaluative goals. The research methodology employed is descriptive analysis and mapping of the existing assessment structure. This study explores the clarity of assessment objectives, the alignment of assessment tools with expected competencies, and the level of stakeholder engagement in the evaluation process. Data were collected through interviews, surveys, and document analysis. The analysis results identified the strengths and weaknesses of the current assessment system, providing a better understanding of its implementation at Okmin University. The findings of this research offer valuable insights to enhance the effectiveness of the assessment and evaluation system in higher education within the university environment. The practical implications of this research can support the development of policies and best practices in improving the quality of higher education at Okmin University.